2017
DOI: 10.18632/oncotarget.14974
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-3 expression increases the malignant potential of lung adenocarcinoma cells: role of epidermal growth factor receptor activation

Abstract: Claudins are essential for the formation and maintenance of tight junctions (TJ). The altered expression of claudin proteins has been described in a variety of malignancies. However, the alteration of these proteins in lung adenocarcinoma (ADC) are poorly understood. Therefore, we report, based on the protein expression analysis of a total of 275 patient samples, that claudin-3 (CLDN3) expression is significantly increased in ADC tissues and is associated with cancer progression, correlating significantly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…In contrast, Zhang et al . have reported that CLND3 expression in AC tissues is upregulated and that CLDN3 overexpression is associated with a poor prognosis 23 . Therefore, we speculated that differential CLDN3 expression in different histological types of lung cancer is related to the origin and development process of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Zhang et al . have reported that CLND3 expression in AC tissues is upregulated and that CLDN3 overexpression is associated with a poor prognosis 23 . Therefore, we speculated that differential CLDN3 expression in different histological types of lung cancer is related to the origin and development process of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, CLDN3 expression is decreased in hepatocellular carcinoma 24 as well as in esophageal SqCC, and loss of CLDN3 expression is associated with the presence of distant metastases 20 . In lung cancer, CLDN3 has been found to be increased in lung AC, but lost in lung SqCC 23 , 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the EGF-induced overexpression of CLDN3 in adenomacarcinoma (ADC) cells reinforces the cell proliferation (65). In another study CLDN3 was suggested to be a potential molecular target for future application in the treatment of ADC (66). It is interesting that almost all of these cell cycle regulatory proteins can be modulated by PI3K signaling (67).…”
Section: Igfbp-3 Expression Level Following Reduction Of Foxa1 Signifmentioning
confidence: 98%
“…Since the role of claudins in the regulation of cancer stem cells is well documented, their correlation with drug resistance and distant metastasis is inevitable and obvious [49,88,89]. In brief, claudin-3 and -6 are correlated with lymph node metastasis in squamous cell lung carcinomas [90,91]. Claudin-4 is highly expressed in primary and metastatic prostate cancer [92] and gastric cancer [93,94].…”
Section: Claudins In Chemoresistancementioning
confidence: 99%